NEED ANALYSIS OF ENGLISH FOR SPECIFIC PURPOSES (ESP) TO INFORMATIC STUDENTS - Rita Karmila Sari; Adhityo Kuncoro; Fajar Erlangga (STKIP PGRI Jombang, 2019)
The aim of the research is to find out 1) the aims of students to learn English; 2) the aspects of English students want to learn, 3) the purpose of learning four English language skills namely reading, writing, speaking, and listening, and 4) the difficulties students face when learning English. This research employs a descriptive analysis method with a qualitative approach. The respondents consist of students taken from six regular classes in an informatics study program. The data are obtained by distributing questionnaires. The result of the research indicates that 1) the main aim of students to learn English is for the needs for finding a job; 2) the students want to learn all aspects of language, especially reading; 3) the students’ main difficulties when learning English are limited vocabulary and insufficient understanding of grammar.